Case Study of Students' Errors in Mathematical Modeling: Analysis Based on Solution Plan Stages in Context-Based Problems - Ni Luh Ayu Gita Saraswati; Sri Andayani; Kadek Yoga Santhika (Jurnal Paedagogy, 2026)
This study aims to analyze students’ errors in solving context-based systems of two-variable linear equations (STLVE) based on the stages of the mathematical modeling solution process. This study employed a qualitative approach with a descriptive case study design. The research subjects consisted of 28 ninth-grade students from one class at a junior high school in Denpasar, Indonesia, from which eight students were selected as interview participants. The primary data consisted of students’ answer sheets from the first summative assessment on the systems of two-variable linear equations topic, as well as interview data obtained from students and mathematics teachers. Data were analyzed qualitatively through the stages of data condensation, data display, and conclusion drawing. Students’ errors were classified and interpreted based on the four stages of the mathematical modeling solution process. The results showed that students’ errors in solving context-based systems of two-variable linear equation problems occurred at all stages of the solution process, with the highest frequency of errors appearing in the advanced stages of mathematical modeling. These errors were influenced by several factors, including limited understanding of contextual information, insufficient practice, weak mastery of solution methods, the tendency to solve problems hastily without verification, and difficulties in relating calculation results back to the given context. The findings indicate that the mathematical modeling solution process can serve as a systematic framework for identifying and understanding students’ errors comprehensively, as well as providing a foundation for developing more meaningful and targeted mathematics learning strategies.